Effects of 2,4-dichlorophenoxyacetic acid on the ventral prostate of rats during the peri-pubertal, pubertal and adult stage - Pochettino, Arístides A. (2016)
Fil: Fil: Pochettino, Arístides A. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Laboratorio de Toxicología Experimental; Argentina.